2016
DOI: 10.1111/fare.12197
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Fatherhood Involvement: The Association Between Father–Child Relationship Quality and Youth Delinquency Trajectories

Abstract: The effect of nonresidential father relationship characteristics on delinquency trajectories among low‐income youth (N = 799) was examined using data from the Three Cities Study, a longitudinal study of mothers and their children eligible for Temporary Assistance for Needy Families in Boston, Chicago, and San Antonio. Growth curve models were employed to track delinquency trajectories and their rate of growth. Characteristics of father–child relationships (anger–alienation, trust–communication) were specified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 76 publications
(98 reference statements)
2
28
2
4
Order By: Relevance
“…Our results are in line with findings of earlier work demonstrating the protective effect of paternal (Yoder et al, 2016) as well as maternal support on adolescent delinquency (Hoeve et al, 2009). Combined with our findings concerning the sibling relationship, these findings suggest that investing specifically in relationships of adolescents with their mothers, fathers as well as siblings may have a mitigating effect on adolescent delinquency development.…”
Section: Family Negativity Is Related To Adolescent Delinquencysupporting
confidence: 92%
“…Our results are in line with findings of earlier work demonstrating the protective effect of paternal (Yoder et al, 2016) as well as maternal support on adolescent delinquency (Hoeve et al, 2009). Combined with our findings concerning the sibling relationship, these findings suggest that investing specifically in relationships of adolescents with their mothers, fathers as well as siblings may have a mitigating effect on adolescent delinquency development.…”
Section: Family Negativity Is Related To Adolescent Delinquencysupporting
confidence: 92%
“…Specifically, the level of delinquent behavior increases when individuals develop from childhood to early adolescence and reaches its peak gradually (i.e., the rate of increase slows down as adolescents age), then declining from late adolescence to adulthood. Such a developmental route has been observed in different cultures [1,3,7,8]. For instance, it was identified that the delinquency level was lower in early adolescents than that in mid-adolescents, while late adolescents demonstrated more delinquent behaviors than did adults [9].…”
Section: Introductionmentioning
confidence: 98%
“…In literature, family processes have been commonly emphasized as utmost important factors that influence adolescent delinquent behavior, because family constitutes the basic ecology where children are socialized and their behavioral patterns are shaped [15]. For example, positive family functioning, parental supervision, and attachment exhibited negative associations with adolescent delinquent behavior [6,16,17], while neglect and a poor parental–child relationship positively predicted adolescent delinquent behavior [8,18]. Among different parental factors, parental control has been emphasized as one critical dimension that is vital to the development of adolescent delinquency [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations